Aplicação de rede de sensores sem fio para a análise do movimento humano - Felipe Augusto Oliveira Mota (2017)
Human Movement Analysis enables qualitative and quantitative data to be collected in order to identify specific patterns and pathologies associated with athletes or ordinary people. The present study focuses on the gait movement, which is directly linked to a persons locomotion and whose analysis is of interest of areas so diversity like health and sport. Considering this, a computational system for data acquisition based on Wireless Sensor Networks was designed and implemented to support the biomechanical gait analysis. This type of network was chosen due to the fact that it made an autonomous, versatile and, mainly, low-cost analysis feasible. The system consists of sensor nodes that can be attached to a persons limbs. Each node contains an ESP8266 platform connected to an MPU6050 module that includes a gyroscope and an accelerometer. Initially, the system operates through a self-tuning (self-calibration) phase. After collecting data, the accelerometer signal is converted to degrees and the gyroscope signal is converted to degrees per second. In the base computer, the gyroscope data are modeled employing a rotation matrix through the application of the Euler angle methods and quaternions. Both sensors outputs are combined by means of a first order complementary filter, and a special mechanical device valids the sensors measurements. After a validation step, tests were performed in individuals with the sensor nodes attached to their lower limbs. It was possible, then, to observe the angles created by the gait movement in the X, Y and Z axes. The results were compared to previously established standards in the literature and they demonstrate that the device can already be used as a low-cost substitute for optical control cameras, which have a much higher cost.